PENGEMBANGAN E-MODUL BERBASIS DISCOVERY LEARNING MENGGUNAKAN SOFTWARE EXE-LEARNING PADA MATERI FUNGSI KELAS X SMA - Haloho, Elysha Jefirayani; Azis, Zainal; Afnaria, Afnaria; Syahlan, Syahlan (Universitas Islam Sumatera Utara, 2024)
The rapid development of science and technology encourages renewal efforts in the utilization of various technological results in the learning process, such as utilizing digital-based learning media. This research aims to produce e-module learning tools based on discovery learning on quadratic function material for class X SMA students that are valid, practical, and effective. The research method used is Research and Development with Thiagarajan 4-D development model: define, design, develop, and disseminate. The subject of this research is the production of e-modules based on the discovery learning model. The object of this research is the students of SMA Negeri 1 Purba, totaling 33 students. The instruments used in this study were validation questionnaires and student responses to the e-modules developed as well as student learning outcomes tests. The results of this study indicate that the e-Module developed has met the requirements of validity and practicality as stated in the results of the questionnaire given. In addition, the e-module developed was also declared effective based on the student learning outcomes test with an average of 78,79% and included in the good category.